(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study is devoted to the study of the grammatical features of headlines in French newspapers. The purpose of the study is to identify and analyze the grammatical principles used in the construction of newspaper headlines in French. As research material, the titles of the newspapers Le Monde, Le Figaro and Libération were selected. Headings were analyzed in terms of grammatical structure, verb forms, articulations and other grammatical features. The results of the study showed that when making headlines in French newspapers, short and concise grammatical structures, simple forms of the verb present and past tense, clear articulations are widely used. Also found in the headings are acquired pronouns and abbreviated forms of adjectives. The results of the study can be used in the teaching of French, in the practice of translation and in the linguistic analysis of newspaper texts.